2.4 GHZ HETERODYNE RECEIVER FOR HEALTHCARE APPLICATION - Cai, Wei; Shi, Frank (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
The objective of this research was to design a basic 2.4 GHz heterodyne receiver for healthcare on a 130um CMOS process. The ultimate goal for the wireless industry is to minimize the trade-offs between performance and cost, and between performance and low power consumption design. In the first part, a low noise amplifier (LNA), which is commonly used as the first stage of a receiver, is introduced and simulated. LNA performance greatly affects the overall receiver performance. The LNA was designed at the 2.4 GHz ISM band, using the cascode with an inductive degeneration topology. The second part of this thesis presents a low power 2.4 GHz down conversion Gilbert Cell mixer. In the third part, a high-performance LC-tank CMOS VCO was designed at 2.4 GHz. The design uses using PMOS cross-coupled topology with the varactor for wider tuning range topology. In the first part, a low noise amplifier (LNA) design reaches the NF of 2 dB, has a power consumption of 2.2 mW, and has a gain of 20dB. The second part of this proposal presents a low power 2.4 GHz down conversion Gilbert Cell mixer. The obtained result shows a conversion gain of 14.6 dB and power consumption of 8.2 mW at a 1.3V supply voltage. In the third part, a high-performance LC-tank CMOS VCO was designed at 2.4 GHz. The final simulation of the phase noise is-128 dBc/Hz, and the tuning range is 2.3 GHz-2.5 GHz while the total power consumption is 3.25 mW. The performance of the receiver meets the specification requirements of the desired standard.